Short-term treatment outcomes of children starting ART in the ICU, general medical wards and outpatient HIV clinics at Red Cross War Memorial Children’s Hospital (RCWMCH): a retrospective cohort study - Pillay, Vashini (Department of Public Health and Family Medicine, 2015)
Includes bibliographical references.